Biomass generation and heterologous isoprenoid milking from engineered microalgae grown in anaerobic membrane bioreactor effluent. (1st February 2023) - de Freitas, Bárbara Bastos; Overmans, Sebastian; Medina, Julie Sanchez; Hong, Pei-Ying; Lauersen, Kyle J.
Highlights: Engineered Chlamydomonas can grow directly in AnMBR effluent. Algal strain grew in modeled environmental conditions of the central Red Sea coast. Algae cleaned N and P from AnMBR effluent and CO2 from off-gas. Engineered strain produced a heterologous sesquiterpene and biomass from effluent. Bio-processes with heavily engineered algae in AnMBR effluent are possible. Abstract: Wastewater (WW) treatment in anaerobic membrane bioreactors (AnMBR) is considered more sustainable than in aerobic reactors. However, outputs from AnMBR are a mixed methane and carbon dioxide gas stream as well as ammonium- (N) and phosphate- (P) containing waters. Using AnMBR outputs as inputs for photoautotrophic algal cultivation can strip the CO2 while removing N and P from effluent which feed algal biomass generation. Recent advances in algal engineering have generated strains that produce high-value side products concomitant with biomass, although only shown in heavily domesticated, lab-adapted strains. Here, it was investigated whether engineered Chlamydomonas reinhardtii could be grown directly in AnMBR effluent with CO2 concentrations found in AnMBR off-gas. The strain was found to proliferate over bacteria in the non-sterile effluent, consume N and P to levels that meet general discharge or reuse limits, and tolerate cultivation in modelled (extreme) outdoor environmental conditions prevalent along the central Red Sea coast. In addition to ∼2.4 g CDW L –1 biomass production in 96 h, a high-value heterologous sesquiterpene co-product could be obtained from 'milking' up to 837 µg L –1 culture in 96 h. This is the first demonstration of a combined bio-process that employs a heavily engineered algal strain to enhance the product generation potentials from AnMBR effluent treatment. This study shows it is possible to convert waste into value through use of engineered algae while also improving wastewater treatment economics through co-product generation. Graphical abstract: Image, graphical abstract